2006
DOI: 10.1186/1742-6413-3-23
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B cell lymphoma of thyroid as a masquerader of anaplastic carcinoma of thyroid, diagnosed by FNA : A case report

Abstract: BackgroundBoth thyroid lymphoma and anaplastic carcinoma of thyroid present with rapidly growing mass in eldery patients. Anaplastic carcinoma has high mortality rate and combination of surgery, radiation therapy and multidrug chemotherapy are the best chance for cure. Prognosis of thyroid lymphoma is excellent and chemotherapy for widespred lymphoms and radiotherapy with or without adjuvant chemotherapy for tumors localized to the gland, are the treatment of choice.Case reportThis article reports a 70 year ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Focusing on IHC, the realization that PTLs are positive for leucocyte common antigen, MS4A1 (CD20), and light chain and negative for cytokeratins on immunohistochemical staining has already improved the sensitivity and specificity of FNAC [61]. A study by Ito et al identified increased expression of CDC25A and CDC25B, which have oncogenic potential, in 47% and 67% of thyroid lymphomas, respectively, using IHC [62].…”
Section: Fine Needle Aspiration Cytologymentioning
confidence: 99%
“…Focusing on IHC, the realization that PTLs are positive for leucocyte common antigen, MS4A1 (CD20), and light chain and negative for cytokeratins on immunohistochemical staining has already improved the sensitivity and specificity of FNAC [61]. A study by Ito et al identified increased expression of CDC25A and CDC25B, which have oncogenic potential, in 47% and 67% of thyroid lymphomas, respectively, using IHC [62].…”
Section: Fine Needle Aspiration Cytologymentioning
confidence: 99%
“…The expression of PAX8 has been studied in C-cell-derived neoplasms with variable results ranging from negativity to focal positivity (13,23,24,27). In doubtful cases, positivity for medullary cancer markers (calcitonin, synaptophysin and chromogranin) is diagnostic (28). High-grade lymphomas closely mimic ATCs on FNA (29).…”
Section: Pax8 Casesmentioning
confidence: 99%
“…While a single cell, dispersed cytologic architectural pattern is typical of lymphoma, ATC cells can occur singly or in dyshesive groups or intermixed with areas of better-differentiated thyroid carcinoma. TL can also be pleomorphic with dispersed cells arranged into tissue fragments and may be indistinguishable from ATC by light microscopy [11]. While the cell block material did contain several cellular groups and single cells, the material was nonetheless quantitatively limited and ultimately did not lead to a specific diagnosis, similar to the experience of others reported in the literature [12].…”
Section: Discussionmentioning
confidence: 83%